The thyroid eye disease (TED) laterality debate: A comparison of characteristics, presentation, severity, and activity, between unilateral and bilateral thyroid eye disease - Ronald Steven S. Medalle II, MD, MBA; Red Thaddeus D. Miguel, MD, MBA (Elsevier, 2022)
Background/objectives: Thyroid eye disease (TED), which can lead to severe sequelae, can involve either one eye or both eyes. The importance of knowing the distinction between laterality rests on the risk that either presentation is associated with a more severe form. It is our aim to investigate differences in patient characteristics and presentations between unilateral and bilateral TED. Methods: Cross-sectional study on clinically diagnosed TED patients from December 2013 to April 2018. Patients' sociodemographic factors, medical history, presentation, severity, and activity between unilateral TED and bilateral TED were compared. Results: 65 patients were included (unilateral TED: n = 40, 61.5%; bilateral TED: n = 25, 38.5%). Unilateral and bilateral TED were not different with regards to age, gender, family history of thyroid disease, comorbidities, and smoking status. There was nearly six times the likelihood of methimazole intake being associated with bilateral TED (odds ratio [OR] = 5.80, p = 0.02). Both groups were similar in almost all general presentation, orbital inflammation signs, and manifestations of lid retraction. The exception being blurred vision that was more common among bilateral TED patients (OR = 4.80, p = 0.04). There were also no differences between both groups in terms of thyroid hormones (TSH: p = 0.84; freeT4: p = 0.12), severity (p = 0.61), and activity (p = 0.99). Conclusions: Our study found unilateral TED to be more prevalent, while ongoing methimazole treatment and blurred vision are associated with bilateral TED. Our findings add to the growing evidence suggesting that the laterality of TED is not a factor in differentiating levels of activity or severity.